A review of piscine islet xenotransplantation using wild‐type tilapia donors and the production of transgenic tilapia expressing a "humanized" tilapia insulin. (5th July 2014) - Wright, James R.; Yang, Hua; Hyrtsenko, Olga; Xu, Bao‐You; Yu, Weiming; Pohajdak, Bill
Abstract Most islet xenotransplantation laboratories have focused on porcine islets, which are both costly and difficult to isolate. Teleost (bony) fish, such as tilapia, possess macroscopically visible distinct islet organs called Brockmann bodies which can be inexpensively harvested. When transplanted into diabetic nude mice, tilapia islets maintain long‐term normoglycemia and provide human‐like glucose tolerance profiles. Like porcine islets, when transplanted into euthymic mice, they are rejected in a CD4 T‐cell‐dependent manner. However, unlike pigs, tilapia are so phylogenetically primitive that their cells do not express α(1, 3)Gal and, because tilapia are highly evolved to live in warm stagnant waters nearly devoid of dissolved oxygen, their islet cells are exceedingly resistant to hypoxia, making them ideal for transplantation within encapsulation devices. Encapsulation, especially when combined with co‐stimulatory blockade, markedly prolongs tilapia islet xenograft survival in small animal recipients, and a collaborator has shown function in diabetic cynomolgus monkeys. In anticipation of preclinical xenotransplantation studies, we have extensively characterized tilapia islets (morphology, embryologic development, cell biology, peptides, etc.) and their regulation of glucose homeostasis. Because tilapia insulin differs structurally from human insulin by 17 amino acids, we have produced transgenic tilapia whose islets stably express physiological levels of humanized insulin and have now bred these to homozygosity. These transgenic fish can serve as a platform for further development into a cell therapy product for diabetes.